Excitatory-inhibitory imbalance in temporal lobe epilepsy: a 5T multimodal MRI biomarker for focus localization and drug resistance stratification - Huang, Zhaodi; Deng, He; Xu, Ying; Shi, Lu; Jiang, Qingjun; Xue, Ke; Li, Ling; Wei, Ying; Xia, Xiaona; Meng, Xiangshui (Frontiers in Aging Neuroscience, 2025)
This study aimed to investigate the diagnostic value of combined glutamate chemical exchange saturation transfer (GluCEST) imaging and γ-aminobutyric acid (GABA)-edited proton magnetic resonance spectroscopy (1H-MRS) in localizing epileptogenic foci and differentiating drug-resistant epilepsy (DR) from drug-responsive epilepsy (DRES) in temporal lobe epilepsy (TLE) using 5T MRI.Twenty-four TLE patients (13 left, 11 right) and 25 age-/gender-matched healthy controls (HCs) underwent GluCEST and MEGA-PRESS MRS at 5T MRI. Directional asymmetry indices (DAIglu_H for hippocampus, DAIglu_A for amygdala) and a novel composite biomarker (DAIglu_GABA) integrating GluCEST asymmetry and GABA/Cr ratios were analyzed. Another asymmetry metric was employed to discriminate the left and right TLE groups [DAIglu_H(epi) for hippocampus, DAIglu_A(epi) for amygdala]. Subgroup comparisons (HC vs. DR vs. DRES) and receiver-operating characteristic (ROC) analyses were performed.ResultsGluCEST-derived hippocampal asymmetry [DAIglu_H(epi)] effectively lateralized epileptogenic foci (AUC = 0.86). The DRES patients exhibited elevated DAIglu_H (adjusted p < 0.001) and reduced GABA/Cr (adjusted p = 0.015) compared to HCs. The DAIglu_GABA index increased in the DRES subgroup compared to HCs (adjusted p < 0.001). Moreover, DAIglu_GABA levels were found to be significantly lower in the DR subgroup in comparison to the DRES subgroup (adjusted p = 0.009).ConclusionMultimodal 5T MRI integrating GluCEST and GABA-MRS provides a clinically feasible tool for lateralizing epileptogenic foci and stratifying drug resistance in TLE. The observed excitatory-inhibitory imbalance dynamics suggest distinct neurometabolic profiles underlying DR and DRES, advancing personalized therapeutic strategies.